Inhibitory Effect of Ferulic Acid and Isoferulic Acid on the Production of Macrophage Inflammatory Protein-2 in Response to Respiratory Syncytial Virus Infection in RAW264.7 Cells - S. Sakai; H. Kawamata; T. Kogure; N. Mantani; K. Terasawa; M. Umatake; H. Ochiai (Mediators of Inflammation)
We investigated the effect of ferulic acid (FA) and isoferulic acid (IFA), which are the main active components of the rhizoma of Cimicifuga heracleifolia (CH), an anti-inflammatory drug used frequently in Japanese traditional medicine, on the production of macrophage inflammatory protein-2 (MIR-2) in a murine macrophage cell line, RAW264.7, in response to respiratory syncytial virus (RSV) infection. Following the exposure of cells to RSV for 20 h, the MIP-2 level in condition medium was increased to about 20 ng/ml, although this level in mock-infected cells was negligible. In the presence of either FA or IFA, RSV-infected cells reduced MIP-2 production in a dose-dependent manner. These data suggest that FA and IFA might be responsible, at least in part, for the anti-inflammatory drug effect of CH extract through the inhibition of MIP-2 production.